Nasal Caffeine Thermo-Sensitive In Situ Gel for Enhanced Cognition after Sleep-Deprivation - Zhu, Siqing; Zhang, Yuanyuan; Li, Qi; Pang, Lulu; Ma, Jinqiu; Wang, Chunqing; Zhang, Shouguo; Jin, Yiguang; Wang, Xiu; Ma, Shan; Li, Liqin; Du, Lina (Current Drug Delivery, 2023)
Background: Caffeine abundant in coffee has a strong excitation effect on the central nerve system (CNS). Methods: To combat the adverse effects of sleep deprivation on physical and mental health, this article designed a new nasal temperature-sensitive gel loaded with caffeine, whose effects of awakening and improving cognition in sleep-deprived rats were evaluated. Results: It was found that the caffeine thermo-sensitive in situ gel (TSG) stayed in the nasal cavity for a longer time and increased the contact time between the drugs and the nasal mucosa, which made it possible for caffeine TSG to exert a lasting effect. Secondly, compared with sleep-deprived rats, those administrated with caffeine TSG were more responsive in behavioral experiments. Moreover, the antipentobarbital test proved that caffeine TSG could prolong the sleep latency and shorten the sleep time. Furthermore, caffeine TSG could significantly restore the cognitive ability by ameliorating neuronal cell injuries by upregulating brain-derived neurotrophic factor (BDNF) levels. Conclusion: Generally, caffeine TSG could quickly exert the efficacy of enhancing cognition and wakefulness, and overcome the drawbacks of frequent medications. It can potentially be used for the treatment of psychiatric disorders, such as dementia, Parkinson and Alzheimer’s disease.
Keywords: Caffeine